Replication of Hepatitis C Virus RNA on Autophagosomal Membranes - Sir, Donna; Kuo, Cheng-fu; Tian, Yongjun; Liu, Helene Minyi; Huang, Eric J.; Jung, Jae U.; Machida, Keigo; Ou, Jing-hsiung James (The Journal of biological chemistry, 2012)
Previous studies indicated that hepatitis C virus (HCV) perturbs the autophagic pathway to induce the accumulation of autophagosomes in cells. To understand the role of autophagosomes in the HCV life cycle, we established a stable Huh7 hepatoma cell line that contained an HCV subgenomic RNA replicon and also expressed a GFP-LC3 fusion protein. The GFP-LC3 protein is localized to autophagosomes during autophagy and served as a convenient marker for autophagosomes. Our results indicate that the silencing of the expression of LC3 or Atg7, two protein factors critical for the formation of autophagosomes, suppresses the replication of HCV RNA. Confocal microscopy studies revealed the localization of HCV NS5A and NS5B proteins, which are two important components of the HCV RNA replication complex, and nascent HCV RNA to autophagosomes. The association of the HCV RNA replication complex with the autophagosomal membranes was further confirmed by co-immunoprecipitation and immunoelectron microscopy studies. Interestingly, inhibition of Class III PI3K activity had no effect on the autophagosomes induced by HCV. These results indicate that HCV induces autophagosomes via a Class III PI3K-independent pathway and uses autophagosomal membranes as sites for its RNA replication. Hepatitis C virus (HCV) induces autophagosomes in its host cells. The HCV RNA replication complex colocalizes with autophagosomes, which are induced by HCV via a Class III PI3K-independent pathway. HCV induces autophagosomes and uses their membranes for its RNA replication. The perturbation of the autophagic pathway by HCV may have important consequences in HCV pathogenesis.